The efficiency of Islamic banks in Malaysia: Based on DEA and Malmquist productivity index / Mohd Faizal Basria, Amirul Afif Muhamat and Mohamad Nizam Jaafar. - Basri, Mohd Faizal; Muhamat, Amirul Afif; Jaafar, Mohamad Nizam (Universit Teknologi MARA Cawangan Selangor, 2018)
This paper aims to investigate the impact of liberalisation move by Bank Negara Malaysia (BNM) towards the efficiency of domestic and foreign Islamic banks (IBs) in Malaysia. This is consequence of decision of BNM that awarded licenses to three international IBs, namely Kuwait Finance House (KFH), Al Rajhi Bank, and Asian Finance Bank in 2005. In addition, this study takes into consideration the existing foreign banks in the country that operate via Islamic banking subsidiaries as part of foreign IBs. The research evaluates the impact of foreign Islamic banks in Malaysia by measuring their contribution to the growth of the Malaysian Islamic banking industry. Using a sample of 16 IBs in Malaysia from 2008 to 2015, the study uses Data Envelopment Analysis (DEA) in measuring the efficiency level of each bank and comparative between the performance of domestic and foreign IBs in the country. The paper also employs the Malmquist Productivity Index to gauge the changes in its components between the same subjects and timeframe. The DEA results showed that the domestic Islamic banks are considered more efficient than most domestic Islamic banks outperforming the foreign Islamic banks. Banks like Hong Leong Islamic, Maybank Islamic, Public Islamic, and RHB Islamic are considered among the top performers for technical efficiency and scale efficiency. The study also found that based on the Malmquist Productivity Index, the least efficient banks based on DEA have improved in technical efficiency, technology, and total factor productivity (TFP).